Globally dangerous diseases: Bad news for Main Street, good news for Wall Street? - Michael Donadelli; Renatas Kizys; Max Riedel (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper examines whether investor mood, driven by World Health Organization (WHO) alerts and media news on globally dangerous diseases, is priced in pharmaceutical companies' stocks in the United States. We concentrate on irrational investors who buy and sell pharmaceutical companies' stocks guided by beliefs as opposed to rational expectations. We argue that disease-related news (DRNs) should not trigger rational trading. We find that DRNs have a positive and significant sentiment effect among investors (on Wall Street). The effect is stronger (weaker) for small (large) companies, who are less (more) likely to engage in the development of new vaccines in the wake of DRNs. A potential negative mood (on Main Street) - induced by disease related fear - does not alter the positive sentiment effect. Our findings give rise to profitable trading strategies leading to significantly positive performances. Overall, this unparalleled research shows that large events of devastating nature to the economy can be considered as good news to some groups of interest, such as stock market traders.
Keywords: G11; G14; I11; 330; WHO alerts; investor sentiment; pharmaceutical industry; trading strategies